ANALISIS RESEPSI AUDIENS PADA KONTEN MY MAKE UP ROUTINE DALAM AKUN TIKTOK @PODCASTKESELAJE - Addin Azkal Azkiyai; Novalia (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the audience's reception of My Make Up Routine content on the TikTok account @podcastkeselaje. The content attracted attention because it depicted anxiety about make-up routines which were considered to indicate a search for social validation. The research method used is qualitative with a reception analysis approach. This research involves interviews with audiences who meet certain criteria, namely TikTok users aged 17-24 years who are aware of and have watched this content. The research results show that there are three positions for the audience's reception of this content: dominant hegemonic position, negotiation position, and opposition position. The dominant hegemonic position was accepted by one informant which is in line with the general view that the content aims to gain social appreciation and show off the make-up collection. The negotiating position was also accepted by one informant who acknowledged the benefits of the content but reminded the importance of maintaining privacy. The oppositional position was taken by four informants who rejected the dominant view and emphasized the educational, inspirational and creative expression value of the content. The majority of informants tended to take an oppositional position, indicating that the audience's views on the content of